Sequence and structural determinants required for priming of plus-strand DNA synthesis by the human immunodeficiency virus type 1 polypurine tract. - Powell, M D (1996)
At the 3' end of all retroviral genomes there is a short, highly conserved sequence known as the polypurine tract (PPT), which serves as the primer for plus-strand DNA synthesis. We have identified the determinants for in vitro priming by the human immunodeficiency virus type 1 (HIV-1) PPT. We show that when the PPT is removed and placed into different nucleotide contexts, new priming sites are produced at the precise 3' end of the PPT. In addition, we find that a hybrid consisting of a 15- or 20-nucleotide RNA primer annealed to a 35-nucleotide DNA template is competent for initiation of plus-strand synthesis with HIV-1 reverse transcriptase. Thus, no cis-acting elements appear to be required for priming activity. Changes at the 5' end of the PPT have no effect on primer function, whereas the identity of bases at the 3' end is crucial. A primer containing only the 6 G residues from the 3' end of the wild-type PPT sequence and 9 bases of random sequence at the 5' end functions like a wild-type PPT. A short hybrid having a similar helical structure but a primary sequence different from that of the PPT is cleaved imprecisely, resulting in initiation of synthesis at multiple sites; however, total primer extension is close to the wild-type level. We conclude that helical structure as well as the presence of particular bases at the 3' end of the PPT is essential for PPT function.